2000
DOI: 10.1046/j.1365-277x.2000.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of dietary carbohydrate as an approach to weight maintenance after initial weight loss: a pilot study

Abstract: Correspondence T. Kirk,Aim To test a novel approach to weight management based on positive advice to eat more carbohydrate-rich foods.Methods Twenty-nine overweight/mildly obese male and female volunteers were recruited. For a 2-week period they were required to replace one main meal each day with a serving of breakfast cereal. This was followed by 4 weeks eating adlib on a high-carbohydrate regime. Each subject, who acted as his/her own control, kept a 3-day unweighed food diary at baseline, 2 weeks and 6 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 12 publications
4
30
0
Order By: Relevance
“…140,146,155 It was not clear whether or not any advice on behaviour change was given in these studies. All of the remaining studies discussed in this chapter provided dietary and exercise advice and behaviour change training, and four of these also provided an exercise programme to attend.…”
Section: Systematic Review Of Uk Interventions With Data For Men or Fmentioning
confidence: 98%
See 1 more Smart Citation
“…140,146,155 It was not clear whether or not any advice on behaviour change was given in these studies. All of the remaining studies discussed in this chapter provided dietary and exercise advice and behaviour change training, and four of these also provided an exercise programme to attend.…”
Section: Systematic Review Of Uk Interventions With Data For Men or Fmentioning
confidence: 98%
“…Of the mixed-sex reports, seven were retrospective cohort studies with follow-up periods ranging from 12 weeks 150 to 24 months. 31 We included two prospective cohort studies, 31,155 which reported data for men at 6 weeks and 12 months respectively. Four reports were of studies using male-orientated sports settings to facilitate recruitment and intervention delivery; two involved four Scottish Premier League (SPL) football clubs 138,141 and two involved one Rugby League club.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…From a potential list of 276 publications, 30 met the criteria as a meal replacement and 20 were eliminated for reasons listed in the Appendix. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Of the remaining 10, four were eliminated for lack of a prospective control arm and six met the criteria for analysis: (1) PMR according to the stated definition, (2) randomized trial comparing PMR to a traditional low calorie diet plan, (3) study duration 43 months, (4) subjects 418 y, (5) no selfreported data included. In the fifth study (ULM), the control group followed an RCD for the first 3 months and then the PMR plan for the subsequent 9 months of treatment.…”
Section: Data Sources and Study Selectionmentioning
confidence: 99%
“…[4][5][6] Weight loss and food consumption of low-glycemic index (GI) food or of carbohydrates have been speculated to improve obesity as well as insulin resistance. [6][7][8] In general, the fat consumption has decreased in the western societies, and therefore the rise in prevalence of obesity needs to be explained by other dietary and environmental factors, for example the increase of simple carbohydrates and the decrease in physical activity. The effect of consumption of a low-fat diet on body weight reduction and on HDL-cholesterol decrease has been debated before, 9,10 illustrating that specific food consumption might have positive as well as negative effects.…”
Section: Introductionmentioning
confidence: 99%